Concrete prepared with rain water as an environmental contribution from the construction - Bedoya-Montoya, Carlos Mauricio; Medina-Restrepo, Carlos Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article describes the preparation of concrete using rain water and its performance compared with those elaborated with conventional drinking water. The samples made were studied in terms of resistance to compressive stress at ages of 1, 3, 7, 14, 28, 56 and 90 days, also analyzing their microstructure by electronic microscopy scanning (EMS) and characterizing the water involved by a certified laboratory. After analyzing the results, it looks likely that the construction of the concrete can be done in a more thoughtful way regarding the use of water resources, without sacrificing its mechanical, stability and aesthetic qualities. In turn, may be thought the possibility to establish a practice that can be replicated in the Colombian context.